Lower Silesian Factory of Nicotine Preparations - Synowiec, Andrzej (Studia Historiae Oeconomicae, 2022)
The state-owned enterprise under the name of Lower Silesian Factory of Nicotine Preparations (Dolnośląska Wytwórnia Preparatów Nikotynowych; DWPN) with its registered office first in Szalejów Dolny and then in Góra Śląska existed in the years 1952–1958. It produced, above all, nicotine sulphate used by farmers for plant protection (primarily to combat extremely widespread aphids). The plant was managed by the Polish tobacco industry, which supplied the raw material in the form of tobacco waste and waste from tobacco plants. The article first presents the post-war demand of Polish agriculture for nicotine preparations and the plans of the tobacco industry to concentrate their production in one place. Initially, nicotine preparations were manufactured in plants in Szalejów Dolny, Góra Śląska and Kraków-Czyżyny. Finally, under the auspices of the tobacco industry, the DWPN company was established, which produced nicotine preparations for the entire Polish agriculture. DWPN produced approximately 40 tons of nicotine sulphate annually. The plant employed an average of 60–70 employees. Economic reasons and a reduction in the demand for nicotine sulphate resulting from the appearance of cheaper and equally effective insecticides on the market made it necessary to liquidate the plant. The company’s facilities were taken over by the Provincial Union of Enterprises of State Industry in Wrocław.